Exhaled nitric oxide in acute exacerbation of pediatric asthma - Ratnawati Ratnawati; V Nguyen; J Morton; R L Henry; P S Thomas (Indonesian Pediatric Society, 2008)
Background Measurement of exhaled nitric oxide (eNO) is a non-invasive and easy method to monitor airway inflammation.Objectives To compare the levels of eNO during and after anexacerbation of asthma, to evaluate the effect of glucocor-ticosteroids (GCS) on the levels of eNO and to correlate eNOwith other markers of inflammation such as symptom scores, FEV 1and sputum eosinophils.Methods The observational study was performed over 24 monthsat a tertiary paediatric hospital. Subjects underwent eNOmeasurement, spirometry and sputum induction during an asthmaexacerbation and then two weeks later. A symptom score wasrecorded everyday for two weeks. All subjects were treated withÃŸ 2 -adrenergic agonists and an oral glucocorticosteroid (GCS).Results Fifteen subjects with acute asthma exacerbation aged 5and 16 years old participated in the study. The mean level ofeNO during the acute exacerbation was significantly higher thaneNO levels at the follow-up visit, 11.2 (95%CI 9.2;13.2) vs. 8.0(95%CI 5.0;11.1) ppb, P=0.03. In the acute exacerbation, eNOcorrelated with sputum eosinophils (P=0.04), but no correlationcould be found between eNO and the other markers ofinflammation during exacerbation or follow up.Conclusions eNO level increased during asthma exacerbation anddecreased after two weeks of glucocorticosteroid therapy.Measurement of eNO is a practical monitoring method inemergency management of asthmatic children.